Intelligent information and database systems. 8th Asian Conference, ACIIDS 2016, Da Nang, Vietnam, March 14-16, 2016, Proceedings /: 8th Asian Conference, ACIIDS 2016, Da Nang, Vietnam, March 14-16, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available